Resilience profiles of elite athletes and their associations with health-related behaviors, well-being, and performance: a latent profile analysis - Chrétien, A.; Hayotte, M.; Vuillemin, A.; d`Arripe Longueville, F. (Psychology of Sport and Exercise, 2024)
Resilience is an important factor in the performances of elite athletes as it helps them overcome the adversity they face on a daily basis. It is a dynamic process with resilience qualities evolving throughout athletes` sporting careers. Recent research has established links between resilience, sports performance, lifestyle, and health-related factors. However, no study has yet focused on the resilience profiles of athletes (i.e., sub-groups of individuals with similar levels of different resilience qualities). The aims of this study were to: (a) explore the resilience profiles of elite athletes, (b) determine the characteristics of these resilience profiles (i.e., health-related behaviors, well-being, perceived social support), and (c) determine the correlates of these profiles at intrapersonal and interpersonal levels. Latent profile analysis was performed on 307 French elite athletes. Results revealed "high resilience" and "moderate resilience" profiles. Athletes with "high resilience" profiles were more likely to be men, exhibit better health-related behaviors, and have higher levels of psychological well-being and perceived performance. High levels of conscientiousness, extraversion, the dimensions of the coach-athlete relationship and the motivational climate were also related to the "high resilience" profile. This study is the first to explore the resilience profiles of elite athletes. The results suggest that a high level of resilience is related to the adoption of health-related behaviors favorable to elite sport. Based on these findings, health promotion programs targeting the concept of resilience should be developed in elite sport centers for athletes, coaches, and parents.